2011
DOI: 10.1507/endocrj.k10e-402
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of primary aldosteronism associated with subclinical Cushing's syndrome

Abstract: Primary aldosteronism (PA) is characterized by autonomous aldosterone hypersecretion from adrenal gland, resulting in low-renin hypertension often accompanied by hypokalemia and metabolic alkarosis. Recent epidemiologic studies have revealed that PA is more common cause of secondary hypertension than previously thought with its higher prevalence (5-15 %) in patients with hypertension [1][2][3][4][5]. Subclinical Cushing's syndrome (SCS) is characterized as subtle cortisol hypersecretion from adrenal tumor but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
92
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 35 publications
9
92
2
Order By: Relevance
“…In agreement with emerging findings from other groups, 5,6,13,14 the above considerations conversely imply that cortisol provides a less than optimal parameter to establish selective catheterization in nonstimulated sequential AVS procedures. This conclusion is reinforced by our findings that metanephrine to normetanephrine and epinephrine to norepinephrine ratios in most nonstimulated AV samples designated nonselective, based on a cortisol-derived selectivity index of 3.0, were well above the range for ratios in PV samples and within the range for the AV samples designated as selective.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with emerging findings from other groups, 5,6,13,14 the above considerations conversely imply that cortisol provides a less than optimal parameter to establish selective catheterization in nonstimulated sequential AVS procedures. This conclusion is reinforced by our findings that metanephrine to normetanephrine and epinephrine to norepinephrine ratios in most nonstimulated AV samples designated nonselective, based on a cortisol-derived selectivity index of 3.0, were well above the range for ratios in PV samples and within the range for the AV samples designated as selective.…”
Section: Discussionsupporting
confidence: 85%
“…Second, the measurement and interpretation of steroid levels in both sampling approaches may have been biased. Immunoassays have inherent limitations; thus, in light of the endogenous differences in the laterality of cortisol secretion, the use of cortisol in the denominator of the SI and LI could have prevented accurate subtyping of PA, as previously reported (20,21). Because the common denominator of both SI and LI determined by C-AVS is cortisol level, the endogenous difference in laterality of cortisol secretion could lead to misinterpretation of S-AVS findings and affect subsequent sub-typing of PA determined by SI and LI, as reported in previous studies (20,21).…”
Section: Discussionmentioning
confidence: 95%
“…Immunoassays have inherent limitations; thus, in light of the endogenous differences in the laterality of cortisol secretion, the use of cortisol in the denominator of the SI and LI could have prevented accurate subtyping of PA, as previously reported (20,21). Because the common denominator of both SI and LI determined by C-AVS is cortisol level, the endogenous difference in laterality of cortisol secretion could lead to misinterpretation of S-AVS findings and affect subsequent sub-typing of PA determined by SI and LI, as reported in previous studies (20,21). Therefore, only the absolute concentrations of aldosterone and cortisol obtained by S-AVS could enable us to evaluate the precise intra-adrenal steroidogenic distribution, i.e., which tumor or intra-adrenal segment is responsible for hyperaldosteronism or autonomous cortisol production.…”
Section: Discussionmentioning
confidence: 95%
“…However, the mRNA levels of steroidogenic enzymes of 3 APAs with co-secretion of cortisol did not show any specific profile. Hiraishi et al also reported that in a histopathological and immunohistochemical study of 3β-HSD and CYP17, CYP11B2 mRNA levels in APAs with subclinical Cushing's syndrome diagnosed with the guideline of a Research Committee for Adrenal Diseases supported by the Japanese Ministry of Health, Labor and Welfare did not show any difference from those in APAs [18].…”
Section: Discussionmentioning
confidence: 96%
“…Piaditis et al have reported that PA with hypercortisolism was observed in 12.1% of 83 adrenal incidentalomas [26]. In Japan, the prevalence was reported to be 15~30% [9,18,27]. Although the reason for the high prevalence of an association with autonomous cortisol secretion in APAs remains unclear, many cases have been described by Japanese investigators and this may have led to greater awareness in Japan [22].…”
Section: Expression Of Steroidogenic Enzymes and Kcnj5 Mrna In Patienmentioning
confidence: 99%